Needs Assessment of Ethical Leadership Development of School Administrators Under Sakon Nakhon Primary Educational Service Area Office 2 - Chantawong, Jarunee; Pheasa, Akkaluck; Steannoppakao, Pornthep (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to study the assessment of needs in developing ethical leadership of school administrators under Sakon Nakhon Primary Educational Service Area Office 2. The sample group used in the research was 338 school administrators and teachers under Sakon Nakhon Primary Educational Service Area Office 2 in the academic year 2024, which were obtained by multi-stage sampling. The research instrument was a 5-level rating scale questionnaire. The actual condition had a reliability between 0.60-1.00, a discrimination power between 0.54-0.93, and a reliability of 0.98. The condition that should be had a reliability between 0.60-1.00, a discrimination power between 0.35-0.95, and a reliability of 0.98. The statistics used in the research were frequency, percentage, mean, standard deviation, confirmatory factor analysis, and the priority index of needs (PNImodified). The results of the research found that: 1. The Reality of Ethical Leadership of School Administrators It was found that the overall level was very high. When considering each component, the overall level is very high and the condition that should be the ethical leadership of school administrators. In the overall level, it is the highest 2. Needs Assessment ethical leadership development of administrators under Sakon Nakhon Primary Educational Service Area Office 2, it was found that there was a need for the development of ethical leadership of school administrators as a whole, which was 0.0435 when considered in descending order (PNImodified), namely good citizenship, responsibility, and trust. 3 . The guidelines for developing ethical leadership of school administrators consist of 3 aspects: good citizenship, responsibility and trust.